PATTERN OF EXTRANODAL INVOLVEMENT IN NON HODGKINS LYMPHOMA: Extranodal Non Hodgkin’s Lymphoma - Bangash, Mussavir Hussain; Hussain, Iftikhar; Zakaria, Manzar; Piracha, Mohammad Nadeem (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To study the anatomical and histomorphological pattern of extranodal non Hodgkin`s lymphoma (NHL).Study Design: Descriptive studyPlace and Duration of Study: The study was carried out at Oncology department Combined Military Hospital Rawalpindi during July 2012 to April 2013.Materials and Methods: All newly diagnosed patients of NHL with extranodal involvement were included in the study. They were categorized as primary extranodal or secondary extranodal lymphomas. Histological pattern and site of involvement were studied.Results: The male to female ratio was 2.2:1 (Male 31, Female 14), and the mean age was 48.16 years (SD=13.40). Primary extranodal involvement was seen in 55.6% of patients. Secondary extranodal involvement was seen in 44.4% of patients. Diffuse large B- cell lymphoma (DLBCL) was the most common type of NHL observed in both primary and secondary extranodal involvement. Gastrointestinal tract was the most common site for primary extranodal involvement and bone marrow was the most common site for secondary extranodal involvement.Conclusion: High frequency of primary extranodal involvement was noted in our study. DLBCL was the most common morphological type observed. Gastrointestinal tract and secondary bone marrow involvement were the most common anatomical sites for primary and secondary extranodal involvement respectively.